DAYS OF THE WEEK AND MONDAY EFFECT ON THE STOCK RETURN OF FOOD AND BEVERAGES COMPANIES THAT LISTED IN INDONESIA STOCK EXCHANGE - admin, Teguh Syaka Marau B1024141022 (Jurnal Manajemen Update, 2019)
AbstractThis study aims to determine and ascertain the effects of days on company returns with Days of the Week Effect and Monday Effect as control variables in the food and beverage sector listed at IDX 2015 - 2017. The independent variables X1 are Days of the Week and X2 are Monday Effect. The dependent variable is Stock Return. The data used in this study are secondary data derived from annual reports of food and beverage companies. The sample is purposive sampling, meaning the sample chosen by the criteria. The criteria selected 11 companies in 3 years. This study uses SPSS version 22 as software to test regression. This study uses Random Effect Model to test the hypothesis. The results of this study indicate that there is no significant effect of Days of the Week and Monday Effect on Stock ReturnKeywords: Days of the Week Effect, Monday Effect, Stock Return. BibliographyAlun Jones Q.C., 1995, Jones On Extradition, First Edition, Sweet & Maxwell, Inggris.Arens, Alvin. A., Elder, Randal. J. And Beasley. Mark. S yang dialihbahasakan oleh Herman Wibowo. (2008). Auditing dan Jasa Assurance Pendekatan Terintegrasi Jilid I. Edisi Kedua belas. Jakarta: Erlangga.Bachtiar, Yanuar, 2009. Day Of The Week Effect Terhadap Return dan Volume Perdagangan Saham LQ45 dan Non LQ45.Beaver, W.H. 1989. Financial Reporting: An Accounting Revolution, 2nd Ed. Englewood Cliffs, NJ: Prentice Hall, IncBrigham, E. F dan J. F. Weston. (1999). Dasar-dasar Manajemen Keuangan, Edisi 9, Erlangga.Cahyaningdyah, D. 2005. Analisis Pengaruh Hari Perdagangan Terhadap Return Saham: Pengujian Week-Four Effect dan Rogalski effect di Bursa Efek Jakarta. Jurnal Ekonomi dan Bisnis. 20(2).Dyl, Edward, 1988, A Possible Explanation of the Weekend Effect, Financial Analysts Journal, May/JuneEisenhardt, Kathleem. (1989). Agency Theory: An Assesment and Review. Academy of Management Review, 14..Fama, Eugene, 1970, Efficient Capital Markets ? A review of theory and empirical work, Journal of Finance Vol. 25, No. 2Harmono, 2009, Manajemen Keuangan Berbasis Balanced Scorecard (Pendekatan Teori, Kasus, dan Riset Bisnis), Bumi Aksara, Jakarta.Husnan, Suad. (1996). Teori Portofolio Dan Analisis Sekuritas. Yogyakarta : UPP AMP YKPN.Husnan, Suad. 2003. Dasar-Dasar Teori Portofolio dan Analisis Sekuritas. Edisi Ketiga. Yogyakarta: UPP AMP YKPN.Husnan, Suad., Enny Pudjiastuti, 2004. Dasar-Dasar Manajemen Keuangan. Edisi Keempat, Yogyakarta, UPP AMP YKPN.Husnan, Suad. 2005. Dasar-dasar Teori Portofolio dan Analisis Sekuritas. Edisi keempat. Yogyakarta: AMP YKPN.Indriantoro, Nur dan Supomo, Bambang (1999).Metodologi Penelitian Bisnis Untuk Akuntansi & Manajemen. Yogyakarta : Penerbit BPFE.Iramani dan Ansyori Mahdi. 2006. Studi Tentang Pengaruh Hari Perdagangan terhadap Return Saham Jurnal Akuntansi dan Keuangan. Vol. 8, No.2, November. Jensen, M.C. and W.H. Meckling. 1976. ?Theory of the firm: Managerial Behavior, Agency Costs and Ownership structure.? Journal of Financial Economics 3.Jogiyanto, 1998, Teori Portofolio dan Analisis Investasi. Edisi pertama. BPFE.Yogyakarta.Jogiyanto, 2007. Sistem Informasi Keperilakuan. Edisi Revisi. Yogyakarta: Andi OffsetKamaluddin. 2004. Studi kelayakan bisnis. Dioma. Malang.Kato, Kiyoshi. 1990. Weekly Patterns in Japanese Stock Exchange, Management Science. Vol. 36, No. 9.Lakonishok, Josef and Edwin Maberly. 1990. The Weekend Effect: Trading Patterns of Individual and Instutional Investors. Journal of Finance. Vol. 45Mehdian, Seyed and Mark J. Perry, 2001, The Reversal of the Monday Effect: New Evidence from US Equity Markets, Journal of Business Finance & Accounting, Sept/Oct.Miller, Edward, 1988, Why a Weekend Effect, Journal of Portfolio Management, Summer.Moleong, Lexy J. (2007) Metodologi Penelitian Kualitatif, Penerbit PT Remaja Rosdakarya Offset, BandungMulyadi dan Anwar. (2009). The day of the week effects in Indonesia, Singapore, and Malaysia stock market. Munich Personal RePec Archive, MPRA Paper No. 16873.Ross, S. A. 1973. The Economic Theory Of Agency. The Principal\'S Problem. The American Economic Review.Santosa, Purbayu Budi dan Ashari. (2014). Analisis Statistik dengan Microsoft Excel dan SPSS. Yogyakarta: Penerbit Andi.Scott,William R.2000.Financial Accounting Theory.USA:Prentice-Hall. Sefiana, Eka. 2009. Pengaruh Penerapan Corporate Governance Terhadap Manajemen Laba Pada Perusahaan Manufaktur Yang Go Public di BEI. Jurnal Riset Akuntansi-Fakultas Ekonomi-Universitas Gunadarma, No. 2 Vol IX.Sugiyono (2015). Metode Penelitian Kombinasi (Mix Methods). Bandung:AlfabetaSupriyono, Edi dan Wibi Wibowo. 2008. Pengaruh Hari Perdagangan Terhadap Return Saham: Pengujian Week-Four Effect di Bursa Efek Jakarta. Utilitas Jurnal Manajemen & Bisnis. Vol. XVI, No. 1. Januari.Tandelilin, Eduardus. 2001, Analisis Investasi dan Manajemen Portofolio Edisi Pertama, Yogyakarta: BPFE-YogyakartaTandelilin, Eduardus dan Algifari. 1999. Pengaruh Hari Perdagangan terhadap Return Saham. Jurnal Ekonomi dan Bisnis Indonesia. Vol.14, No. 4. Oktober.Wolk, et al (2000). Accounting Theory : A Conceptual Institutional Approach. Fifth Edition. South-Western College Publishing